Screening of Litchi (Litchi Chinensis Sonn.) Genotypes Against Sun Burn (Bangladesh Journal of Botany, 2022)
Thirty genotypes were evaluated for incidence of sun burn and fruit cracking. Fourteen genotypes were affected by sun burn with maximum in genotype IC-0615602 (54.48%). Sixteen genotypes were free from sun burn which possessed maximum cuticle thickness ranging from 1.99 mm in IC-0615585 to 1.95 mm in IC-0615595 whereas susceptible genotypes possessed least thickness of cuticle. Tolerant genotypes possessed maximum fruit skin strength, number of leaflet per shoot, densely spaced leaflet, minimum length of rachis and petioles. Fruit Surface Temperature (FST) of susceptible genotypes was higher than that of tolerant genotypes. Fruits located in the south direction were highly affected to sun burn to the tune of 62.45 % whereas north direction showed least (43.46 %). Positively correlation of sun burn was found with FST (0.83), leaflet interval (0.69), petiole length (0.49) and negatively correlation with cuticle thickness (-0.69), spongy layer thickness (-0.79), fruit skin strength (-0.68) and total leaflet (-0.65).Bangladesh J. Bot. 51(1): 37-43, 2022 (March)